Mechanisms of tumor-associated macrophages affecting the progression of hepatocellular carcinoma - Yuan, Yi; Wu, Dailin; Li, Jing; Huang, Dan; Zhao, Yan; Gao, Tianqi; Zhuang, Zhenjie; Cui, Ying; Zheng, Da-Yong; Tang, Ying (Frontiers in Pharmacology, 2023)
Tumor-associated macrophages are essential components of the immune cell stroma of hepatocellular carcinoma. TAMs originate from monocytic myeloid-derived suppressor cells, peripheral blood monocytes, and Kupffer cells. The recruitment of monocytes to the HCC tumor microenvironment is facilitated by various factors, leading to their differentiation into TAMs with unique phenotypes. TAMs can directly activate or inhibit the nuclear factor (NF)-κB, interleukin-6/ signal transducer and signal transducer and activator of transcription 3, Wnt/β-catenin, transforming growth factor-β1/ bone morphogenetic protein, extracellular signal-regulated kinase 1/2 signaling pathways in tumor cells and interact with other immune cells via producing cytokines and extracellular vesicles, overexpressing related proteins, thus affecting carcinoma cells proliferation, invasive and migratory ability, angiogenesis, liver fibrosis progression, and other processes to participate in different stages of tumor progression. In recent years, TAMs have received much attention as a prospective treatment target for HCC. This review describes the origin and characteristics of TAMs and their mechanism of action in the occurrence and development of HCC to offer a theoretical foundation for further clinical research of TAMs.